Muhkam dan Mutasyabih Dalam Al-Qur'an: Implikasi Teologis dari Al-Muhkam dan Al-Mutasabbih dalam Al-Qur'an - Luthfi Hana Fadiah; Deden Suparman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Investigates the idea of muhkam and mutasyabih stanzas in the Qur'an and the connected religious ramifications. Muhkam refrains are stanzas that have clear, unequivocal and express implications, giving a strong legitimate premise and standards in Islamic lessons. Mutasyabih verses, on the other hand, contain symbolism and metaphors that enhance the spiritual and intellectual aspects of the sacred text and have meanings that are ambiguous and necessitate in-depth analysis. This study demonstrates that muhkam verses provide Muslims with clear practical and legal guidance, whereas mutasyabih verses encourage deep reflection and the development of theological understanding by analyzing the characteristics, functions, and purposes of these two types of verses. In interpreting the Qur'an, where muhkam and mutasyabih verses complement one another in conveying the Divine message, the study emphasizes the significance of a comprehensive and holistic understanding. These verses have important theological implications for the development of contemporary Islamic thought, including a deeper comprehension of God's nature, the essence of Islamic teachings, and the dynamics of interpreting sacred tex.